General Principles in the Commercial Code of France of 1807 - Anna Klimaszewska (Journal on European History of Law, 2011)
No general part was created in the French Code de commerce of 1807, which was one of the basic objections to this act since its very beginnings. Book I was in fact entitled Of Commerce in General, however, even superficial analysis of its content indicates irrefutably that it contained regulations governing a specific subject matter. The lack of a general part did not mean that codifiers were not guided in the works on the code by any higher principles. On the contrary, while creating or copying given standards from earlier binding acts, they realised a legislative policy which had been adopted in advance, and which, paradoxically, did not aim at creating a liberal background for trade, but at managing the economic crisis with intense state control.